Study of charge behavior during solar particle acceleration - G. Hebrero; L. del Peral; D. Rodríguez Frías; G. Balderas Aviles; J. Pérez Peraza; A. Gallegos Cruz (Geofísica Internacional, 2008)
In order to explain the evolution with energy of the charge state of solar par-ticles we have developed a model where charge states are defined at the source during the particle acceleration process. Charge-interchange processes between the accelerated ions and local matter are considered on basis of electron loss and capture cross-sections at high energies. The model is worked out under two different approaches. We apply the model to observational data of charge states of most of particle events published in the literature. We discuss our results and implications within the frame of other existing models: we conclude that our analyticaldeveloped by other authors.